Mandapa and Mukhamandapa of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) and mukhamandapa (front porch) of the Undeshwar feature elaborate moldings and low walls that uphold intricately carved kakshasana (seat back). Niches on the walls of the mukhamandapa and mandapa are adorned with carvings depicting deities such as Kartikeya, avatars (manifestations) of Vishnu, and the ashta dikapalas (deities representing eight cardinal directions).